Developing key competencies in education some lessons from international and national experience - Rychen, Dominique Simone; Tiana, Alejandro (Studies in comparative education, 2004)
The world must address such priorities as technological change, globalization, identity, inequality, poverty, conflicts, and signs of ecological distress. Education contributes to social well-being and political stability. In the light of these global challenges, which competencies are important?